A8.11 gilz-dependent activin a production by MSC inhibits TH17 differentiation. (31st January 2014) - Luz-Crawford, P; Tejedor, G; Ipseiz, N; Pène, J; Morand, E; Beaulieu, E; Jorgensen, C; Noël, D; Djouad, F
Abstract : Background and Objectives: Together with B cells, Th1 and Th17 cells are the immune cell subsets mainly associated with the development of autoimmune diseases. Mesenchymal stem cells (MSC) display immunosuppressive properties via the inhibition of T cell activation and proliferation. Recent evidences have shown that MSC negatively regulate both Th1 and Th17 responses and restore the balance between T-helper and T regulatory cells. However, the molecular mechanisms by which mouse MSC exert their immunosuppressive effect on Th1 and Th17 cells have not been fully elucidated. We investigated the role of Gilz, an anti-inflammatory protein expressed by MSC. Material and Methods: We used MSC isolated from the bone marrow of wild-type (WT MSC) or Gilz-deficient (Gilz -/- MSC) mice. T cells obtained from the spleen of WT mice were differentiated into Th1 or Th17 cells. After 6 days of T cell/MSC coculture, proliferation was quantified and the number of IFN-γ- and IL-17-producing Th1 and Th17 cells, respectively, was measured by flow cytometry. Using ELISA, we quantified the production of Activin A, PGE2 and NO2 in the supernatants of differentiated Th1 or Th17 cells in the presence or absence of MSC. Phosphorylation of Smad-2/-3 in CD4 + T cells induced to differentiate into Th17 cells was determined using an ELISA-based assay using fluorogenic substrates kit. Results: In the coculture assay, the presence of Gilz -/- MSC decreased the proliferation rate of CD4 + T cell differentiating into Th1 or Th17, although to a lesser extent compared to WT MSC. Moreover, while WT MSC significantly decrease the percentage of CD4 + T cells undergoing Th1 and Th17 polarization, Gilz -/- MSC displayed a reduced suppressive effect on CD4 + T cell differentiation. The impaired immunomodulatory functions of Gilz -/- MSC were accompanied by their reduced capacity to produce NO2 and Activin A as compared to WT MSC. Finally, we showed that under Th17 skewing conditions, the release of Activin A by WT MSC repressed the Th17 differentiation program through Smad3/2 activation and promoted the generation of IL-10 producing CD4 + T cells. Conclusion: Our data indicate that Gilz-dependent production of Activin A participates in the inhibition of Th17 cell development by MSC . Thereby, via Gilz expression, MSC offer a potential mean of impacting on autoimmune diseases mediated by Th17 cells.